MeHg Developing Exposure Causes DNA Double-Strand Breaks and Elicits Cell Cycle Arrest in Spinal Cord Cells - Fabiana F. Ferreira; Dib Ammar; Gilian F. Bourckhardt; Karoline Kobus-Bianchini; Yara M. R. Müller; Evelise M. Nazari (Journal of Toxicology, 2015)
The neurotoxicity caused by methylmercury (MeHg) is well documented; however, the developmental neurotoxicity in spinal cord is still not fully understood. Here we investigated whether MeHg affects the spinal cord layers development. Chicken embryos at E3 were treated in ovo with 0.1 μg MeHg/50 μL saline solution and analyzed at E10. Thus, we performed immunostaining using anti-γ-H2A.X to recognize DNA double-strand breaks and antiphosphohistone H3, anti-p21, and anti-cyclin E to identify cells in proliferation and cell cycle proteins. Also, to identify neuronal cells, we used anti-NeuN and anti-βIII-tubulin antibodies. After the MeHg treatment, we observed the increase on γ-H2A.X in response to DNA damage. MeHg caused a decrease in the proliferating cells and in the thickness of spinal cord layers. Moreover, we verified that MeHg induced an increase in the number of p21-positive cells but did not change the cyclin E-positive cells. A significantly high number of TUNEL-positive cells indicating DNA fragmentation were observed in MeHg-treated embryos. Regarding the neuronal differentiation, MeHg induced a decrease in NeuN expression and did not change the expression of βIII-tubulin. These results showed that in ovo MeHg exposure alters spinal cord development by disturbing the cell proliferation and death, also interfering in early neuronal differentiation.